Education and Social Trust: Testing a Causal Hypothesis Using the Discordant Twin Design. Issue 3 (27th April 2016) - Oskarsson, Sven; Thisted Dinesen, Peter; Dawes, Christopher T.; Johannesson, Magnus; K. E. Magnusson, Patrik
Abstract : One of the clearest results in previous studies on social trust is the robust positive relationship with educational attainment. The most common interpretation is that education has a causal effect on social trust. The theoretical argument and empirical results in this article suggest a different interpretation. We argue that common preadult factors such as cognitive abilities and personality traits rooted in genes and early‐life family environment may confound the relationship between educational attainment and social trust. We provide new evidence on this question by utilizing the quasi‐experiment of twinning. By looking at the relationship between education and social trust within monozygotic (MZ) twin pairs, we are able to avoid potential confounders rooted in genetic factors and common environmental influences because the monozygotic twins share both. The results suggest that when controlling for such familial factors the estimated effects of education on social trust are close to zero and far from reaching statistical significance. Further analyses show that the relationship between education and social trust largely is driven by common genetic factors.